Digital Problem-Based Worksheet with 3D Pageflip: An Effort to Address Concept Understanding Problems and Enhance Digital Literacy Skills - Distrik, I. W.; Ertikanto, C.; Purwati, Y. S.; Saregar, A.; Ab Rahman, N. F. (Jurnal Pendidikan IPA Indonesia, 2024)
This study aims to provide digital teaching materials in the form of problem-based worksheets with 3D PageFlip presentations that are valid, practical, and effective in overcoming conceptual understanding problems and enhancing digital literacy skills in high school students. The research approach employed was a mixed method based on Thiagarajan’s (1974) 4D development model, which consists of four stages: define, design, develop, and disseminate. Three experts conducted the validity test and a limited field test involving ten high school students. Furthermore, the large-scale field test was carried out at another high school with 60 students utilizing the static pretest-post-test design. Data for the study were gathered through observation, tests, and questionnaires. Qualitative data analysis was done descriptively using the percentage technique, while quantitative data was analyzed using statistical tests. According to the results, the problem-based digital worksheet with the 3D PageFlip display has an average content validity of 8.83 and an average construct validity of 8.91. It has been proven practical with a digital worksheet implementation rate of 89.39 and positive student responses. Conceptual understanding that occurs before learning can be overcome through images and videos embedded in digital worksheets. The difference in concept knowledge and digital literacy progress between the experimental and control groups demonstrates the usefulness of this teaching material. Thus, problem-based digital worksheet teaching materials with 3D PageFlip can overcome conceptual understanding problems and improve students’ digital literacy.